Investigation the anterior mandibular lingual concavity by using cone-beam computed tomography - M. Çitir (Folia Morphologica, 2021)
BACKGROUND: In the presence of lingual concavity in the mandible, the cortical perforation and consequently the life-threatening intraoral haemorrhages obstructing the upper respiratory tract may be seen during the surgical intervention. The present study was aimed to determine the prevalence of lingual concavity in the interforaminal region and its relationship with gender and dentate status. MATERIALS AND METHODS: The images of 106 patients who underwent cone-beam computed tomography (CBCT) between 2016 and 2017 in Department of Dental and Maxillofacial Radiology Department of Faculty of Dentistry of Ondokuz Mayıs University were retrospectively examined. The images were obtained using a Galileos device (98 kVp, 15–30 mA). The bone height and width in interforaminal region and the frequency of lingual concavity were analysed. RESULTS: Of patients involved in the present study, 42.5% were male and 57.5% were female After the examinations performed, the bone was morphologically classified into four classes as type I lingual concavity, type II inclined to lingual, type III enlarging towards labiolingual and type IV buccal concavity. Type III (77.9%) was the most common type in the anterior region, followed by type II (16.5%), type I (4.7%) and type IV (0.9%). The lingual concavity angle was 76.5 ± 3.69º and the concavity depth was 2.09 ± 0.34 mm. CONCLUSIONS: The lingual concavity can be detected by using the cross-sectional CBCT images and the complications related with lingual cortical perforation can be prevented.